Eco-Friendly Farming: Gen Z's Farming Style By Developing Organic Pesticides - Safarinda Nurdianawati (Journal of Innovative and Creativity, 2025)
The study, entitled "Eco-Friendly Farming: Gen Z Farming Style by Developing Organic Pesticides," aims to determine the level of understanding, attitudes, and abilities of Agrotechnology students at Halim Sanusi University in developing organic pesticides as a form of environmentally friendly farming. This study involved 20 students using qualitative descriptive methods through observation, interviews, and documentation. The results showed that students have a high awareness of the importance of maintaining agricultural ecosystems and quite good skills in creating organic pesticides from natural ingredients such as neem leaves, lemongrass, and garlic. The resulting organic pesticide products have proven effective in reducing pest attacks by up to 65% on horticultural crops. This study also revealed that Gen Z farming style is not only oriented towards harvest results, but also pays attention to environmental sustainability and agricultural technology innovation. These findings indicate that Agrotechnology students have the potential to become agents of change in realizing a sustainable agricultural system in the future. This research is expected to serve as a reference for the development of green-minded agricultural education and encourage the implementation of environmentally friendly innovations among the younger generation.